Evaluation of current status, threats and means of protection of heaths Arctostaphylo-Callunetum R.Tx. et Prsg 1940 in the Czerwony Bór (NE Poland) - Łaska, Grażyna (Ecological Questions, 2015)
The study was performed to identify, delimit and evaluate the current status of Arctostaphylo-Callunetum R.Tx. et Prsg 1940 heaths, as well as to point out possible threats to these communities and means of their protection. The heaths are in Czerwony Bór (PLH 200018) in Podlaskie voivodeship, NE Poland, in the area included in the Natura 2000 network. The study was performed in 2008 with the use of GPS method over the study area of 3,784.04 ha. The area of Czerwony Bór includes 8 stands with dry heaths of Arctostaphylo-Callunetum of the total area of 21.7 ha. They are represented by typically developed and well-preserved patches of vegetation (90%) of the area of 19.5 ha and not so well preserved patches (10%) occupying the area of 2.2 ha. In general, their natural value in the area of study is high and the representative character, degree of preservation of the structure and functions are excellent. The main threat to the dry heaths Arctostaphylo-Callunetum in the area of Czerwony Bór comes from the forest management procedures aimed at reclamation of the area left after the army training grounds, reforestation in the form of large-area single-species forest plantations, forestation of the land that has not been forested earlier. In the areas where no plantation have been started the process of secondary succession is observed. As a result of this process heaths are replaced by forest-thicket formations. The active protection of the heaths in the area studied should include prevention of secondary succession, mowing and removal of forest-thicket formations and changes in forest management policy towards maintenance of open space by periodical removal of vegetation to bare soil.